The Concept of Public Financial Policy in Islam Abu Ubaid al-Qasimy's Perspective - Ridho, Ali; Hazirin, Muhammad Fariz (Yapilin Press, 2025)
The public financial management system includes state revenues and expenditures which include kharaj, zakat, jizyah, ushur, and ghanimah. This system aims to create justice and optimize state revenue. Second, Abu Ubaid emphasized the importance of fair, transparent, and community-friendly distribution of public finances, as well as maintaining the balance of economic power to reduce inequality. The application of these principles requires fair policies, strict supervision, and the use of public funds to meet social needs, in order to achieve social justice and stability in society. This research uses a library research approach to explore the concept of public financial policy in Islam from the perspective of Abu Ubaid al-Qasimy. This method was chosen because it allows for an in-depth study of a wide range of relevant literature, including primary texts such as the Kitab al-Amwal by Abu Ubaid al-Qasimy as well as secondary literature that discusses his thoughts.